Potensi Antibakteri Ekstrak Bulu Babi Diadema setosum dan Echinometra Mathaei : Literature Review - Natalia Michelle Simatupang; Ramadhan Triyandi; Ihsanti Dwi Rahayu; Femmy Andrifianie; Muhammad Iqbal (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The increasing incidence of bacterial resistance to antibiotics has become one of the major challenges in global health, necessitating the exploration of natural antibacterial sources as alternative treatments, such as bioactive compounds derived from sea urchins. This literature review aims to evaluate the antibacterial potential of sea urchin extracts based on existing research findings. The literature search was conducted using the PubMed and Google Scholar databases using the Boolean operators (AND, OR). Inclusion criteria include articles published between 2014 and 2024, available in full text, written in either Indonesian or English, and discussing the antibacterial activity of sea urchin extracts from the species Diadema setosum and/or Echinometra mathaei. Based on the selection process, eight articles met the inclusion criteria and were included in the review. The results of the literature review indicate that sea urchin extracts exhibit antibacterial activity against gram-negative bacteria, including Escherichia coli, Salmonella typhi, Salmonella typhimurium, Shigella flexneri, Pseudomonas aeruginosa, Aeromonas hydrophila, Acinetobacter sp., Citrobacter freundii, and Klebsiella pneumoniae, as well as gram-positive bacteria, including Propionibacterium acnes, Staphylococcus aureus, Bacillus cereus, Bacillus subtilis, Staphylococcus epidermidis, Streptococcus mutans, and Streptococcus sobrinus. These antibacterial effects are attributed to the presence of secondary metabolites such as alkaloids, steroids, flavonoids, saponins, and phenolics.